OPTIMASI PEMANFAATAN MATERIAL LOKAL UNTUK LAPIS FONDASI PERKERASAN JALAN - Nyoman Suaryana; Silvester Fransisko (Jurnal Jalan-Jembatan, 2019)
Local material in the form of a mixture of sand and stone, including limestone is commonly found in Indonesia which at the moment generally cannot be used directly for pavement foundation because of its low quality (substandard). The use of these local materials for pavement foundation layers is very important, especially in the outermost and remote areas that do not have quality material sources as specified in specifications such as on the NTT - Timor Leste border, Trans Papua and Talaud Islands Regency North Sulawesi Province. This study aims to determine the effect of stabilization with cement to optimize the strength of the local materials. The study was carried out by experimental methods through laboratory testing. The results showed that the stabilization of the local materials with cement can produce a fairly high compressive strength value. The value of compressive strength is higher according to the increasing percentage of cement content used. Referring to the value of the compressive strength produced (in general 24-40 kg/cm2), the local material can be used for the pavement foundation layer, and for the use or application in the field, specifications are needed as recommended by this study.Key words: pavement foundation layers, substandard local material, sirtu, cement stabilization, compressive strength